Menthone Exerts its Antimicrobial Activity Against Methicillin Resistant Staphylococcus aureus by Affecting Cell Membrane Properties and Lipid Profile - Zhao W; Yang C; Zhang N; Peng Y; Ma Y; Gu K; Liu X; Liu X; Liu X; Liu Y; Li S; Zhao L (Dove Medical Press, 2023)
Wenming Zhao,1,2,* Chengwei Yang,1,* Ning Zhang,3,* Yuanyuan Peng,3 Ying Ma,3 Keru Gu,3 Xia Liu,3 Xiaohui Liu,3 Xijian Liu,3 Yumin Liu,4 Songkai Li,1 Linjing Zhao3 1Department of Spinal Surgery, The 940th Hospital of Joint Logistics Support Force of PLA, Lanzhou, People's Republic of China; 2Department of Orthopedics, Zhangye Second People's Hospital, Zhangye, People's Republic of China; 3College of Chemistry and Chemical Engineering, Shanghai University of Engineering Science, Shanghai, People's Republic of China; 4Instrumental Analysis Centre, Shanghai Jiao Tong University, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Linjing Zhao, College of Chemistry and Chemical Engineering, Shanghai University of Engineering Science, Shanghai, People's Republic of China, Email ljzhao@sues.edu.cn Songkai Li, Department of Spinal Surgery, The 940th Hospital of Joint Logistics Support Force of PLA, Lanzhou, People's Republic of China, Email lisongkai@gmail.comObjective: The characteristic constituents of essential oils from aromatic plants have been widely applied as antimicrobial agents in the last decades. However, their mechanisms of action remain obscure, especially from the metabolic perspective. The aim of the study was to explore the antimicrobial effect and mechanism of menthone, a main component of peppermint oil, against methicillin resistant Staphylococcus aureus (MRSA).Methods: An integrated approach including the microbiology and the high-coverage lipidomics was applied. The changes of membrane properties were studies by the fluorescence and electron microscopical observations. The lipid profile was analyzed by ultra-high performance liquid chromatography coupled with quadruple Exactive mass spectrometry (UHPLC-QE-MS). The lipid-related key targets which were associated with the inhibitory effect of menthone against MRSA, were studied by network analysis and molecular docking.Results: Menthone exhibited antibacterial activities against MRSA, with minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of 3,540 and 7,080 μg/mL, respectively. The membrane potential and membrane integrity upon menthone treatment were observed to change strikingly. Further, lipids fingerprinting identified 136 significantly differential lipid species in MRSA cells exposed to menthone at subinhibitory level of 0.1× MIC. These metabolites span 30 important lipid classes belonging to glycerophospholipids, glycolipids, and sphingolipids. Lastly, the correlations of these altered lipids, as well as the potential metabolic pathways and targets associated with menthone treatment were deciphered preliminarily.Conclusion: Menthone had potent antibacterial effect on MRSA, and the mechanism of action involved the alteration of membrane structural components and corresponding properties. The interactions of identified key lipid species and their biological functions need to be further determined and verified, for the development of novel antimicrobial strategies against MRSA.Keywords: menthone, MRSA, antimicrobial activity, cell membrane, lipid homeostasis, microbial lipidomics, UHPLC-QE-MS